Analisis Kinerja Pdam Tirta Siak Provinsi Riau Kota Pekanbaru - Shifa, Indah Kamelya; Sandhyavitri, Ari; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The objectives of this research study were to asses Pekanbaru water supply company (PDAM Tirta Siak) performances during period of 2010 to 2014 based on BPPSPAM Dirtjen Cipta Karya regulation year 2010 and Kepmendagri No. 47 year 1999. Statistical analysis were than dipployed in this study. Four major indicators of water supply company indicators performances were investigated as the following aspecs; financial, services, operationals and human resources. It was identified that based on the BPPSPM regulation an average of this company performances was 2,05 (ill categories <2,2). Mean while based on the Kepmendagri regulation an average of this company performances was 36,01 (not healthy categories <4,5).The reason of these low performances because of the following issues: low human resources skills, high rate of non revenue water(NRW>50%), and low water quality.Keyword :performances analysis, quality, recommendation, water, Pekanbaru City